Current collector and preparation method thereof, secondary battery and electric device
Patent Information
- Application Number
- CN202380061473.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2025-04-01
AI Technical Summary
When iron-nickel alloy foil is used as a current collector in existing secondary batteries, problems such as increased battery impedance, performance attenuation, and internal short circuit are likely to occur, affecting the service life.
A current collector design is adopted that includes a first metal layer of iron element or iron alloy and a metal stack formed of copper, tin, lead, molybdenum, chromium, nickel and other elements. The strength and anti-corrosion performance of the current collector are improved through the stacked structure and gradient design. , to prevent direct contact between iron and electrolyte.
It effectively extends the service life of secondary batteries, reduces production costs, improves energy density and mechanical strength, and reduces the corrosion of iron by water and HF in the electrolyte.
Smart Images

Figure CN119744457A_ABST
Abstract
Description
Current collector and preparation method thereof, secondary battery and electric device Technical Field
[0001] The present application relates to the technical field of battery materials, and in particular to a current collector and a preparation method thereof, a secondary battery, and an electrical device. Background Art
[0002] In recent years, as the application scope of secondary batteries has become increasingly wider, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, aerospace and other fields.
[0003] As secondary batteries have made significant progress, higher requirements have been placed on their energy density and production costs. Related technologies use iron-nickel alloy foil, a uniform mixture of iron and nickel, as the current collector. Due to its lightweight and low cost, iron-nickel alloy foil offers significant advantages in increasing the energy density and reducing costs of secondary batteries.
[0004] However, after a period of use, secondary batteries using iron-nickel alloy foil as current collectors may experience problems such as increased battery impedance, performance degradation, and internal short circuits, which shorten the service life of the secondary batteries and limit the application of such current collectors in secondary batteries.
[0005] Therefore, seeking a current collector that can extend the service life of a secondary battery is one of the research directions that those skilled in the art focus on.
[0006] Summary of the Invention
[0007] The present application is made in view of the above-mentioned problems, and one of its objectives is to provide a current collector that can extend the service life of a secondary battery.
[0008] To achieve the above-mentioned objectives, the first aspect of the present application provides a current collector comprising a base layer, a first metal layer, and a second metal layer, wherein the first metal layer is disposed on at least one surface of the base layer, and the second metal layer is disposed on a surface of the first metal layer facing away from the base layer, wherein the first metal layer comprises a single element of iron or an iron alloy; and the second metal layer comprises at least one of a metal layer formed by any one element selected from the group consisting of copper, tin, lead, molybdenum, chromium, and nickel, a single metal laminate formed by any two or more elements, and an alloy layer formed by any two or more elements. Thus, the first metal layer in the current collector comprises a single element of iron or an iron alloy, which can provide the current collector with higher strength. The second metal layer can prevent the iron in the first metal layer from directly contacting the electrolyte, effectively inhibiting corrosion of the iron by water and HF in the electrolyte, thereby ensuring the strength of the current collector and effectively extending the service life of secondary batteries using the iron-containing current collector.
[0009] In any embodiment, the first metal layer is an iron metal layer, and the second metal layer is a nickel metal layer. Thus, compared to conventional copper foil current collectors, current collectors using iron and nickel as the metal layer have lower material costs. Furthermore, at the same thickness, current collectors using iron and nickel are lighter than copper foil current collectors, which can reduce the weight proportion of the current collector in the secondary battery, thereby increasing the energy density of the secondary battery.
[0010] In any embodiment, multiple first metal layers and multiple second metal layers are alternately disposed on the same side surface of the base layer, and the outermost layer of the current collector is the second metal layer. Thus, while the content of each element in the current collector remains the same, the elongation at break and the fracture strength of the current collector can be further improved.
[0011] In any embodiment, in a direction from the base layer toward the outermost layer, the thicknesses of the multiple first metal layers on the same side surface of the base layer are equal.
[0012] In any embodiment, the thickness of the multiple first metal layers on the same side surface of the base layer decreases gradually from the base layer toward the outermost layer. This creates a gradient design for the thickness of the first metal layer, further reducing corrosion of the iron in the first metal layer by water, HF, etc. in the electrolyte.
[0013] In any embodiment, the thickness of the multiple first metal layers on the same side of the base layer decreases from the base layer toward the outermost layer, and the difference in thickness between any two adjacent first metal layers is 0.5 μm to 1.0 μm. That is, the thickness of the multiple first metal layers on the same side of the base layer decreases from the base layer toward the outermost layer by a difference of 0.5 μm to 1.0 μm. This can effectively reduce corrosion of iron by water and HF in the electrolyte, reduce the proportion of electrode corner fractures, and reduce the concentration of iron dissolved in the current collector.
[0014] In any embodiment, in a direction from the base layer toward the outermost layer, the thicknesses of the plurality of second metal layers on the same side surface of the base layer are equal.
[0015] In any embodiment, the thickness of the multiple second metal layers on the same side surface of the base layer increases sequentially from the base layer toward the outermost layer. This allows for a gradient design of the second metal layer thickness, with a thicker second metal layer formed on the outer layer of the current collector, further reducing corrosion of the iron in the first metal layer by water and HF in the electrolyte.
[0016] In any embodiment, the thickness of the multiple second metal layers on the same side of the base layer increases gradually from the base layer toward the outermost layer, and the difference in thickness between any two adjacent second metal layers is 0.5 μm to 1.0 μm. That is, the thickness of the multiple second metal layers on the same side of the base layer increases gradually from the base layer toward the outermost layer, with a difference of 0.5 μm to 1.0 μm. This can effectively reduce corrosion of iron by water and HF in the electrolyte, reduce the proportion of electrode corner fractures, and reduce the concentration of iron dissolved in the current collector.
[0017] In any embodiment, the base layer comprises elemental iron or an iron alloy. The base layer can serve as a supporting layer when preparing the current collector, supporting the first metal layer and the second metal layer. Using elemental iron or an iron alloy as the base layer can also improve the strength of the current collector and reduce costs.
[0018] In any embodiment, the material of the base layer is the same as that of the first metal layer, and the material of the base layer is different from that of the second metal layer.
[0019] In any embodiment, the base layer is a ferrous metal layer.
[0020] In any embodiment, the first metal layer is a ferrous metal layer.
[0021] In any embodiment, the second metal layer is a nickel metal layer.
[0022] In any embodiment, the thickness of the base layer is 2 μm to 6 μm.
[0023] In any embodiment, the thickness of the base layer is 2 μm to 4 μm.
[0024] In any embodiment, the thickness of the current collector is 4 μm to 20 μm. This can provide the current collector with a higher mechanical strength and prevent the current collector from being too thick or too heavy, thereby improving the energy density of the secondary battery.
[0025] In any embodiment, the thickness of the current collector is 6 μm to 9 μm.
[0026] In any embodiment, the thickness of the first metal layer is 0.5 μm to 16 μm.
[0027] In any embodiment, the thickness of the first metal layer is 0.5 μm to 1.5 μm.
[0028] In any embodiment, the thickness of the second metal layer is 0.5 μm to 16 μm. In this way, the thickness of the second metal layer is neither too thin nor too thick, which can ensure good corrosion protection for the iron in the first metal layer and help improve the energy density of the secondary battery.
[0029] In any embodiment, the thickness of the second metal layer is 0.5 μm to 1.5 μm.
[0030] The second aspect of the present application provides a method for preparing the current collector of the first aspect of the present application, comprising the following steps:
[0031] providing a base layer;
[0032] forming a first metal layer on a surface of the base layer; and
[0033] forming a second metal layer on a surface of the first metal layer facing away from the base layer;
[0034] The first metal layer includes iron, and the second metal layer includes any one of copper, tin, lead, molybdenum, chromium and nickel, or an alloy of two or more thereof.
[0035] In any embodiment, the first metal layer and the second metal layer are formed on the substrate layer by electroplating. Electroplating can be used to easily and conveniently prepare the current collector of the embodiment of the present application. The thickness of each metal layer can be controlled by controlling the electroplating process parameters.
[0036] A third aspect of the present application provides a secondary battery comprising a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector, a negative electrode active material being provided on the negative electrode current collector, and the negative electrode current collector comprises the current collector of the first aspect of the present application. As a result, the secondary battery is less susceptible to problems such as increased battery impedance, performance degradation, and internal short circuits caused by corrosion of iron in the current collector by components in the electrolyte, and has a longer service life.
[0037] In any embodiment, the mass fraction of the silicon-based material in the negative electrode active material is 25% to 100%. Thus, the secondary battery utilizes a high-silicon negative electrode plate. Because the negative electrode current collector of the secondary battery utilizes the current collector of the first aspect of the present application, it can better withstand the frequent volume expansion and contraction of the high-silicon negative electrode plate, and is less likely to experience problems such as current collector fracture and separation of the active material from the current collector.
[0038] A fourth aspect of the present application provides an electrical device comprising the secondary battery of the third aspect of the present application.
[0039] The first metal layer in the current collector of the present application includes iron or an iron alloy, and the second metal layer includes at least one of a metal layer formed by any one element selected from copper, tin, lead, molybdenum, chromium, and nickel, a single metal layer formed by any two or more elements, and an alloy layer formed by any two or more elements; the first metal layer and the second metal layer are stacked, and the second metal layer is arranged on the surface of the first metal layer facing away from the substrate layer. The first metal layer in the current collector includes iron or an iron alloy, which can make the current collector have higher strength. The second metal layer can prevent the iron in the first metal layer from directly contacting the electrolyte, effectively inhibiting the iron from being corroded by water and HF in the electrolyte, and ensuring the strength of the current collector. This can, to a certain extent, solve the problems of increased impedance, performance degradation, internal short circuit, etc. of batteries using iron-nickel alloy foil current collectors, and effectively extend the service life of secondary batteries using iron-containing current collectors. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to better describe and illustrate the embodiments and / or examples of the present application, reference may be made to one or more of the accompanying drawings. The additional details or examples used to describe the accompanying drawings should not be considered as limiting the scope of the disclosed application, the presently described embodiments and / or examples, and any of the best modes currently understood for these applications.
[0041] FIG1 is a schematic structural diagram of a current collector according to an embodiment of the present application;
[0042] FIG2 is a schematic structural diagram of a current collector according to another embodiment of the present application;
[0043] FIG3 is a schematic structural diagram of a current collector according to another embodiment of the present application;
[0044] FIG4 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0045] FIG5 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG4 ;
[0046] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0047] Explanation of the reference numerals: 1. Current collector; 11. Base layer; 12. First metal layer; 13. Second metal layer; 5. Secondary battery; 51. Housing; 52. Electrode assembly; 53. Cover plate; 6. Electrical device. DETAILED DESCRIPTION
[0048] Below, the embodiments of the current collector and its preparation method, secondary battery and electric device of the present application are described in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0049] The "ranges" disclosed herein are defined in terms of lower and upper limits, where a given range is defined by selecting a lower limit and an upper limit, and the selected lower and upper limits define the boundaries of the particular range. Ranges defined in this manner can be inclusive or exclusive of the end values and can be combined arbitrarily, i.e., any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60 to 120 and 80 to 110 are listed for a particular parameter, it is understood that ranges of 60 to 110 and 80 to 120 are also contemplated. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, the following ranges are all contemplated: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4, and 2 to 5. In this application, unless otherwise indicated, the numerical range "a to b" is a shorthand representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0050] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0051] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0052] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0053] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0054] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0055] The weights described in this specification may be weight units known in the chemical industry, such as μg, mg, g, and kg.
[0056] At present, due to the great development of secondary batteries, higher requirements have been put forward for the energy density and cost of secondary batteries. In order to improve the energy density of secondary batteries and reduce production costs, the related art uses iron-nickel alloy foil formed by uniformly mixing iron and nickel as electrode current collectors. Since iron-nickel alloy foil has the characteristics of light weight and low cost, it has obvious advantages in improving the energy density and reducing costs of secondary batteries. However, since the electrode current collector needs to directly contact the electrolyte, and the potential of Fe is low and it is easy to corrode, the water and HF in the electrolyte will corrode the Fe in the current collector, thereby causing problems such as increased battery impedance, performance degradation, internal short circuit, etc., affecting the service life of the secondary battery and limiting the application of this electrode current collector in the secondary battery. In response to this, the inventors have discovered a current collector that uses a first metal layer and a second metal layer of a stacked structure and uses a specific material. It can not only improve the energy density of the secondary battery and reduce production costs, but also inhibit the corrosion of Fe in the current collector by water and HF in the electrolyte, thereby making the secondary battery have a longer service life.
[0057] Referring to Figures 1, 2 and 3, in some embodiments, the first aspect of the present application provides a current collector 1, comprising a base layer 11, a first metal layer 12 and a second metal layer 13; the first metal layer 12 is disposed on at least one surface of the base layer 11, and the second metal layer 13 is disposed on the surface of the first metal layer 12 facing away from the base layer 11, the first metal layer 12 comprises iron element or an iron alloy, and the second metal layer 13 comprises at least one of a metal layer formed by any one element of copper, tin, lead, molybdenum, chromium and nickel, a single metal stack formed by any two or more elements, and an alloy layer formed by any two or more elements.
[0058] Traditional electrode current collectors use alloy foils with uniform distribution of iron and nickel elements. The locations where the iron elements are located on the current collector surface are weak points of corrosion. Since the current collector needs to be in contact with the electrolyte in the secondary battery, and the water, HF, etc. in the electrolyte have a corrosive effect on iron; therefore, when using iron-nickel alloy foils with uniform distribution of elements in secondary batteries, during battery circulation and storage, especially under high temperature conditions, the iron elements on the current collector surface may react with water to generate inorganic substances that are deposited on the surface of the electrode, increasing the battery impedance and triggering other side reactions; the iron elements on the current collector surface will also react with HF to cause iron dissolution and deposition, which will also increase the battery impedance and ultimately affect the battery performance.
[0059] The chemical formulas for the reaction between the iron in the current collector 1 and the water, oxygen, and HF in the electrolyte are shown in the following chemical formulas 1, 2, and 3, respectively:
[0060] Chemical formula 1: 3Fe+4H2O=Fe3O4+4H2↑ (under high temperature conditions);
[0061] Chemical formula 2: 4Fe + 3O2 + 2nH2O = 2(Fe2O3 * nH2O) (at room temperature and with O2 in the electrolyte);
[0062] Chemical formula 3: Fe+2HF=FeF2+H2.
[0063] The first metal layer 12 in the current collector 1 of the embodiment of the present application includes a single element of iron or an iron alloy, and the second metal layer 13 includes at least one of a metal layer formed by any one element of copper, tin, lead, molybdenum, chromium, and nickel, a single metal layer formed by any two or more elements, and an alloy layer formed by any two or more elements; the first metal layer 12 and the second metal layer 13 are stacked, and the second metal layer 13 is provided on the surface of the first metal layer 12 facing away from the base layer 11. In the current collector 1 of the embodiment of the present application, the first metal layer 12 includes a single element of iron or an iron alloy, which can make the current collector 1 have higher strength. The second metal layer 13 can prevent the iron in the first metal layer 12 from directly contacting the electrolyte, effectively inhibiting the iron from being corroded by water and HF in the electrolyte, and ensuring the strength of the current collector 1. This can, to a certain extent, solve the problems of increased battery impedance, performance degradation, internal short circuit, etc., and effectively extend the service life of secondary batteries using iron-containing current collectors.
[0064] It is understood that the second metal layer 13 can be a single metal layer formed by any one element of copper, tin, lead, molybdenum, chromium, and nickel; a single metal laminate formed by any two or more elements of copper, tin, lead, molybdenum, chromium, and nickel; or an alloy layer formed by any two or more elements of copper, tin, lead, molybdenum, chromium, and nickel. It is understood that a single metal laminate formed by two or more elements refers to a metal laminate formed by superimposing a single metal layer of one element on a single metal layer of another element.
[0065] In some embodiments, the first metal layer 12 is an iron metal layer, and the second metal layer 13 is a nickel metal layer. Thus, compared to conventional copper foil current collectors, current collectors 1 using iron and nickel metal layers have lower material costs, which can reduce the production cost of secondary batteries. Furthermore, current collectors 1 using iron and nickel are lighter than copper foil current collectors of the same thickness, which can reduce the weight proportion of current collectors 1 in the secondary battery, thereby increasing the energy density of the secondary battery.
[0066] In traditional technology, copper foil is usually used as the negative electrode current collector of secondary batteries. The elongation at break of copper foil current collectors is generally between 3% and 5%, and the fracture strength is generally between 300 MPa and 500 MPa. In high-energy-density secondary batteries, the negative electrode active material contains silicon-based materials that account for 25% to 100% of the total weight of the active material. The volume change of silicon during the lithium insertion process is 120% to 300%. The huge volume change causes the membrane to expand in three dimensions, which puts a great test on the elongation at break and the fracture strength of the negative electrode current collector. If the performance of the negative electrode current collector is insufficient, problems such as separation of the negative electrode active material and the current collector and fracture of the current collector may occur, thereby causing the battery performance to deteriorate. This problem will become more serious as the content of silicon-based materials in the negative electrode active material increases. In the embodiment of the present application, iron metal is used as the first metal layer 12. Its high strength can improve the elongation at break and the fracture strength of the current collector 1, so that the current collector 1 has high mechanical strength. In particular, when the current collector 1 is used as a high-silicon negative electrode current collector, it can better withstand the frequent volume expansion and contraction caused by silicon lithium insertion and delithiation during charging and discharging compared to copper foil, reducing the probability of current collector 1 breakage and peeling of the membrane and current collector 1.
[0067] Referring to Figures 2 and 3 , in some embodiments, multiple first metal layers 12 and multiple second metal layers 13 are alternately disposed on the same side surface of the base layer 11, and the outermost layer of the current collector 1 is the second metal layer 13. In this manner, a current collector 1 can be formed having multiple first metal layers 12 and multiple second metal layers 13 alternately stacked on the surface of the base layer 11. This further improves the elongation at break and the fracture strength of the current collector 1 while maintaining the same element content.
[0068] It should be noted that the number of first metal layers 12 and second metal layers 13 on the same side surface of the base layer 11 can be set according to actual needs. However, the number of first metal layers 12 and second metal layers 13 should not be too large, as this will increase the manufacturing process flow. Generally, the number of first metal layers 12 and second metal layers 13 on the same side surface of the base layer 11 is 1 to 4.
[0069] Referring to FIG. 2 , in some embodiments, the thickness of the multiple first metal layers 12 on the same side surface of the base layer 11 is equal, as measured from the base layer 11 toward the outermost layer. In some embodiments, the thickness of the multiple second metal layers 13 on the same side surface of the base layer 11 is equal, as measured from the base layer 11 toward the outermost layer. That is, each first metal layer 12 and each second metal layer 13 in the current collector 1 is configured to have equal thickness.
[0070] Referring to Figure 3 , in some embodiments, the thickness of the multiple first metal layers 12 on the same side surface of the base layer 11 decreases sequentially from the base layer 11 toward the outermost layer. In other words, the thickness of each first metal layer 12 gradually decreases from the base layer 11 toward the outermost layer. This arrangement allows the first metal layer 12 to be thicker near the inner layer of the current collector 1 and thinner near the outer layer of the current collector 1, creating a gradient thickness design for the first metal layer 12. This further helps reduce corrosion of iron caused by water and HF in the electrolyte.
[0071] In some embodiments, the thickness of the multiple first metal layers 12 on the same side surface of the base layer 11 decreases sequentially from the base layer 11 toward the outermost layer, such that the thickness difference between any two adjacent first metal layers 12 is 0.5 μm to 1.0 μm. That is, from the base layer 11 toward the outermost layer, the thickness of the inner first metal layer 12 is 0.5 μm to 1.0 μm greater than the thickness of the adjacent outer first metal layer 12. This can effectively reduce corrosion of iron caused by water and HF in the electrolyte, reduce the rate of electrode corner fracture, and reduce the concentration of iron dissolved in the current collector 1.
[0072] It is understood that the term "adjacent layers" does not mean that they are physically in contact with each other, but rather that the first metal layers 12 are located adjacent to each other in the plurality of layers arranged on the same side surface of the base layer 11 in the aforementioned direction. It is understood that the thickness difference of the first metal layers 12 can be, but is not limited to, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, and 1.0 μm.
[0073] In some embodiments, the thickness of multiple second metal layers 13 on the same side surface of the base layer 11 increases sequentially from the base layer 11 toward the outermost layer. That is, the thickness of each second metal layer 13 gradually increases from the base layer 11 toward the outermost layer. This arrangement allows the second metal layer 13 to be thicker near the outer layer of the current collector 1 and thinner near the inner layer of the current collector 1, forming a gradient design for the thickness of the second metal layer 13. The thicker second metal layer 13 formed on the outer layer of the current collector 1 can further reduce corrosion of iron by water, HF, and other substances in the electrolyte.
[0074] In some embodiments, the thickness of multiple second metal layers 13 on the same side surface of the base layer 11 increases sequentially from the base layer 11 toward the outermost layer, such that the thickness difference between any two adjacent second metal layers 13 is 0.5 μm to 1.0 μm. That is, from the base layer 11 toward the outermost layer, the thickness of the inner second metal layer 13 is 0.5 μm to 1.0 μm less than the thickness of the adjacent outer second metal layer 13. This can effectively reduce corrosion of iron caused by water and HF in the electrolyte, reduce the rate of electrode corner fracture, and reduce the concentration of iron dissolved in the current collector 1.
[0075] It is understood that the term "adjacent layers" does not mean that they are physically in contact with each other, but rather that the second metal layers 13 are located adjacent to each other in the plurality of layers arranged on the same side surface of the base layer 11 in the aforementioned direction. It is understood that the thickness difference of the second metal layers 13 may be, but is not limited to, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, and 1.0 μm.
[0076] In some embodiments, the base layer 11 is made of elemental iron, that is, an iron metal layer, and has a thickness of 2 μm to 6 μm. This base layer 11 serves as a plating carrier layer when forming the first metal layer 12 and the second metal layer 13. The thickness of the base layer 11 should not be too thick, otherwise it will increase the weight of the current collector 1. Furthermore, using an iron metal layer for the base layer 11 can also improve the strength of the current collector 1 and reduce its cost.
[0077] In some embodiments, the thickness of the current collector 1 is 4 μm to 20 μm. It is understood that the thickness of the current collector 1 includes the thickness of the first metal layer 12 and the second metal layer 13 described above, as well as the thickness of the base layer 11. The thickness of the current collector 1 should not be too thin or too thick. Too thinness will reduce the mechanical strength of the current collector 1, while too thickness will increase the volume and weight of the current collector 1. It is understood that the thickness of the current collector 1 can be, but is not limited to, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, or 20 μm.
[0078] In some embodiments, the thickness of the current collector 1 is 6 μm to 9 μm.
[0079] In some embodiments, the thickness of the first metal layer 12 is 0.5 μm to 16 μm. That is, the thickness of each first metal layer 12 is within the range of 0.5 μm to 16 μm. It is understood that the thickness of the first metal layer 12 can be, but is not limited to, 0.5 μm, 1.0 μm, 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, 10.0 μm, 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, 15.0 μm, or 16.0 μm.
[0080] In some embodiments, the thickness of the first metal layer 12 is 0.5 μm to 1.5 μm.
[0081] In some embodiments, the thickness of the second metal layer 13 is 0.5 μm to 16 μm. That is, the thickness of each layer of the second metal layer 13 is within the range of 0.5 μm to 16 μm. The thickness of the second metal layer 13 should not be too thin or too thick. Too thinness will reduce the anti-corrosion effect on iron, and too thickness will increase the volume and weight of the current collector 1. It can be understood that the thickness of the second metal layer 13 can be but is not limited to 0.5 μm, 1.0 μm, 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, 10.0 μm, 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, 15.0 μm, and 16.0 μm.
[0082] In some embodiments, the thickness of the second metal layer 13 is 0.5 μm to 1.5 μm.
[0083] In some embodiments, the second aspect of the present application provides a method for preparing the current collector 1 of the first aspect of the present application, comprising the following steps: providing a base layer 11; forming a first metal layer 12 on a surface of the base layer 11; and forming a second metal layer 13 on a surface of the first metal layer 12 facing away from the base layer 11. The first metal layer 12 comprises a single element of iron or an iron alloy, and the second metal layer 13 comprises at least one of a metal layer formed by any one element of copper, tin, lead, molybdenum, chromium, and nickel, a single metal layer formed by two or more elements, and an alloy layer formed by two or more elements.
[0084] In some embodiments, the first metal layer 12 and the second metal layer 13 are formed on the base layer 11 by electroplating. By electroplating, the current collector of the first aspect of the present application can be prepared simply and conveniently. Moreover, the thickness of each metal layer can be conveniently controlled by controlling the electroplating process parameters. It is understood that the method of forming the first metal layer 12 and the second metal layer 13 on the base layer 11 in the present application is not limited to electroplating, and the first metal layer 12 and the second metal layer 13 can also be formed by other existing methods such as sputtering.
[0085] In some embodiments, after forming the second metal layer 13, the first metal layer 12 and the second metal layer 13 can be sequentially formed on the outer side of the second metal layer 13. In this way, a current collector can be formed with multiple alternating first and second metal layers 12, 13. The thickness gradient of each first metal layer 12 and each second metal layer 13 can be varied by controlling the electroplating process parameters. The number of first and second metal layers 12, 13 can be controlled by the number of alternating electroplating cycles.
[0086] In some embodiments, the third aspect of the present application provides a secondary battery comprising a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte. The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material disposed on the negative electrode current collector. The negative electrode current collector employs the current collector of the first aspect of the present application. As a result, the secondary battery is less susceptible to problems such as increased battery impedance, performance degradation, and internal short circuits caused by corrosion of iron in the current collector by components in the electrolyte, and has a longer service life.
[0087] In some embodiments, the mass fraction of silicon-based materials in the negative active material on the negative electrode sheet is 25% to 100%. In high-energy-density secondary batteries, the negative electrode sheet usually contains silicon-based materials that account for a large proportion of the total mass of the negative active material. Silicon undergoes a huge volume change during the lithium insertion process, causing the negative active material layer to extend in three dimensions, making it easy for the negative active material to peel off from the negative current collector, the negative current collector to break, and other problems to occur, resulting in a sharp decline in battery performance, and this problem will be aggravated as the content of silicon-based materials in the negative material increases. The secondary battery of the present application adopts the current collector of the first aspect of the present application. Compared with the traditional copper foil current collector, the current collector has a higher elongation at break and fracture strength. When used as the negative current collector of a high-silicon secondary battery, it can better withstand frequent volume expansion and contraction, and is less likely to have problems such as current collector breakage and peeling of the active material from the current collector.
[0088] It can be understood that the silicon-based material can be selected from at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites and silicon alloys; the mass fraction of the silicon-based material in the negative electrode active material on the negative electrode sheet can be but is not limited to 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88%, 90%, 92%, 95%, 98%, 100%.
[0089] In some embodiments, the fourth aspect of the present application further provides an electrical device, which includes the secondary battery of the third aspect of the present application.
[0090] The secondary battery and the electric device of the present application will be described below with reference to the accompanying drawings as appropriate.
[0091] Unless otherwise specified, the components, material types, or contents of the batteries mentioned are applicable to both lithium-ion secondary batteries and sodium-ion secondary batteries.
[0092] In one embodiment of the present application, a secondary battery is provided.
[0093] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During the battery's charge and discharge processes, active ions are inserted and removed between the positive and negative electrodes. The electrolyte conducts ions between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing ions to pass through.
[0094]
Positive electrode
[0095] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector.
[0096] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.
[0097] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc. Polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.)
[0098] In some embodiments, the positive electrode active material may include a positive electrode active material for a battery known in the art.
[0099] As an example, the positive electrode active material of a lithium-ion secondary battery may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds. Examples of olivine-structured lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0100] As an example, the positive electrode active material of a sodium ion secondary battery may include at least one of the following materials: a sodium transition metal oxide, a polyanionic compound, and a Prussian blue compound. However, the present application is not limited to these materials, and other conventionally known materials that can be used as positive electrode active materials for sodium ion batteries may also be used.
[0101] As an optional technical solution of the present application, in the sodium transition metal oxide, the transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. Sodium transition metal oxide is, for example, Na x MO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0<x≤1.
[0102] As an optional technical solution of the present application, the polyanionic compound can be a compound having sodium ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y can be at least one of P, S and Si; n represents (YO4) n- valence.
[0103] Polyanionic compounds can also be sodium ions, transition metal ions, tetrahedral (YO4) n- A class of compounds containing anion units and halogen anions. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y can be at least one of P, S, and Si, and n represents (YO4) n- valence state; the halogen may be at least one of F, Cl and Br.
[0104] Polyanionic compounds can also be sodium ions, tetrahedral (YO4) n- Anion unit, polyhedron unit (ZO y ) m+ and an optional halogen anion. Y can be at least one of P, S and Si, and n represents (YO4) n-valence state; Z represents a transition metal, which may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce, and m represents (ZO y ) m+ valence state; the halogen may be at least one of F, Cl and Br.
[0105] Polyanionic compounds include NaFePO4, Na3V2(PO4)3 (sodium vanadium phosphate, abbreviated as NVP), Na4Fe3(PO4)2(P2O7), NaM'PO4F (M' is one or more of V, Fe, Mn and Ni) and Na3(VO y )2(PO4)2F 3-2y At least one of (0≤y≤1).
[0106] Prussian blue compounds can be sodium ions, transition metal ions and cyanide ions (CN - ) compounds. The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. Prussian blue compounds are, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.
[0107] The weight ratio of the positive electrode active material in the positive electrode film layer is 80 to 100 weight %, based on the total weight of the positive electrode film layer.
[0108] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorinated acrylate resin. The weight ratio of the binder in the positive electrode film layer is 0 to 20 weight percent, based on the total weight of the positive electrode film layer.
[0109] In some embodiments, the positive electrode film layer may also optionally include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode film layer is 0 to 20% by weight, based on the total weight of the positive electrode film layer.
[0110] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, wherein the positive electrode slurry has a solid content of 40% by weight (wt%) to 80% by weight, and the viscosity at room temperature is adjusted to 5000 mPa·s (mPa·s) to 25000 mPa·s, the positive electrode slurry is coated on the surface of the positive electrode collector, and after drying, the positive electrode sheet is formed by cold rolling; the positive electrode powder coating unit area density is 25 mg / cm2 (mg / cm 2 )~45mg / cm 2 The compacted density of the positive electrode is 3.0 g / cm3 (g / cm 3 )~3.6g / cm 3 , optional 3.3g / cm 3 ~3.5g / cm 3 .
[0111] The calculation formula for compacted density is:
[0112] Compaction density = coating surface density / (thickness of the electrode after extrusion - thickness of the current collector).
[0113] The mass M of the positive electrode active material per unit area of the positive electrode membrane can be obtained by weighing using a standard balance.
[0114] The thickness T of the positive electrode film can be measured using a micrometer, for example, a Mitutoyo 293-100 with an accuracy of 0.1 μm. It should be noted that the thickness of the positive electrode film described in this application refers to the thickness of the positive electrode film after cold pressing and compaction and used in the positive electrode sheet assembled into the battery.
[0115]
Negative electrode
[0116] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0117] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0118] In some embodiments, the negative electrode current collector adopts the current collector of the first aspect of the present application.
[0119] In some embodiments, the negative electrode active material may be a negative electrode active material for batteries known in the art.
[0120] As an example, the negative electrode active material of a lithium-ion secondary battery may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0121] As an example, the negative electrode active material of a sodium ion secondary battery is generally a hard carbon material, a two-dimensional metal carbide or a nitride. Preferably, the negative electrode active material of a sodium ion secondary battery is generally a hard carbon material.
[0122] The weight ratio of the negative electrode active material in the negative electrode film layer is 70 to 99 weight %, based on the total weight of the negative electrode film layer.
[0123] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode film layer is 0 to 30% by weight, based on the total weight of the negative electrode film layer.
[0124] In some embodiments, the negative electrode film layer may further include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode film layer is 0 to 20% by weight, based on the total weight of the negative electrode film layer.
[0125] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener (e.g., sodium carboxymethyl cellulose (CMC-Na)). The weight ratio of the other additives in the negative electrode film layer is 0 to 15% by weight, based on the total weight of the negative electrode film layer.
[0126] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry, wherein the solid content of the negative electrode slurry is 30wt% to 70wt%, and the viscosity at room temperature is adjusted to 2000mPa·s to 10000mPa·s; the obtained negative electrode slurry is coated on the negative electrode current collector, and after a drying process, cold pressing, such as rolling, is performed to obtain the negative electrode sheet. The negative electrode powder coating unit area density is 6mg / m2 ~13 mg / m 2 The compacted density of the negative electrode is 1.2 g / m3 (g / m 3 )~2.0g / m 3 .
[0127] The mass M of the negative electrode active material per unit area of the negative electrode membrane can be obtained by weighing using a standard balance.
[0128] The thickness T of the negative electrode film can be measured using a micrometer, for example, a Mitutoyo 293-100 with an accuracy of 0.1 μm. It should be noted that the thickness of the negative electrode film in this application refers to the thickness of the negative electrode film after cold pressing and used in the negative electrode sheet assembled into the battery.
[0129] Electrolytes
[0130] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0131] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0132] In some embodiments, the electrolyte salt of the lithium ion secondary battery can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0133] The electrolyte salt of the sodium ion secondary battery can be selected from one or more of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium difluorophosphate, sodium perchlorate, and sodium chloride.
[0134] The concentration of the electrolyte salt is generally 0.5 mol / liter (mol / L) to 5 mol / L.
[0135] In some embodiments, the solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).
[0136] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0137]
Isolation film
[0138] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.
[0139] In some embodiments, the material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0140] In some embodiments, the thickness of the isolation film is 6 μm to 40 μm, and optionally 12 μm to 20 μm.
[0141] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.
[0142] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0143] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0144] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG4 shows a secondary battery 5 having a square structure as an example.
[0145] In some embodiments, referring to Figure 5, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0146] In some embodiments, the secondary batteries 5 can be assembled into a battery module. The number of secondary batteries 5 contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0147] In the battery module, the plurality of secondary batteries 5 can be arranged in sequence along the length of the battery module. Of course, they can also be arranged in any other manner. Furthermore, the plurality of secondary batteries 5 can be fixed by fasteners.
[0148] Optionally, the battery module may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0149] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.
[0150] A battery pack may include a battery box and multiple battery modules disposed within the box. The battery box comprises an upper case and a lower case. The upper case can be placed over the lower case to form an enclosed space for accommodating the battery modules. The multiple battery modules can be arranged in any manner within the battery box.
[0151] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0152] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0153] Figure 6 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0154] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0155] The following are some examples.
[0156] In order to make the technical problems, technical solutions and beneficial effects solved by this application clearer, the application will be further described in detail below with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of this application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is in no way intended to limit the present application and its applications. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0157] If no specific techniques or conditions are specified in the examples, the experiments were carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. All reagents or instruments used without specifying the manufacturer are commercially available conventional products.
[0158] 1. Preparation Example
[0159] 1. Preparation of current collector
[0160] Preparation Example 1
[0161] Using a base layer as a carrier layer, the current collector is formed by electroplating the base layer with an Fe layer multiple times, followed by a Ni layer multiple times. From the outermost layer to the innermost layer of the current collector, the Ni metal layer and the Fe metal layer are sequentially formed on the same side of the base layer. The base layer is a 2μm thick iron metal layer, and the thicknesses of the Ni and Fe metal layers are shown in Table 1.
[0162] Preparation Example 2
[0163] The preparation method of this embodiment is basically the same as that of Preparation Example 1, with the only difference being that the thicknesses of the Ni layer and the Fe layer are different. The thicknesses of the Ni metal layer and the Fe metal layer in this preparation example are shown in Table 1.
[0164] Preparation Example 3
[0165] The preparation method of this embodiment is basically the same as that of Preparation Example 1, with the only difference being that the thicknesses of the Ni metal layer and the Fe metal layer are different. The thicknesses of the Ni metal layer and the Fe metal layer in this preparation example are shown in Table 1.
[0166] Preparation Example 4
[0167] Using the base layer as a carrier layer, multiple electroplating steps were performed on the base layer's surface, followed by multiple electroplating steps of a Ni+Cr alloy layer, to produce a current collector. From the outermost layer toward the innermost layer of the current collector, the Ni+Cr alloy layer and the Fe metal layer were sequentially formed on the same side of the base layer. The base layer was identical to that in Preparation Example 1, and the thicknesses of the Ni+Cr alloy layer and the Fe metal layer are shown in Table 1.
[0168] Preparation Example 5
[0169] Using the base layer as the carrier layer, the surface of the base layer was electroplated with an Fe layer multiple times, followed by a Mo layer multiple times, to produce a current collector. From the outer layer toward the inner layer of the current collector, the Mo metal layer and the Fe metal layer were sequentially formed on the same side of the base layer. The base layer was the same as that in Preparation Example 1, and the thicknesses of the Mo and Fe metal layers are shown in Table 1.
[0170] Preparation Example 6
[0171] The preparation method of this embodiment is basically the same as that of Preparation Example 5, with the only difference being that the Mo metal layer is replaced with a Cr metal layer. The thicknesses of the Cr metal layer and the Fe metal layer in this preparation embodiment are shown in Table 1.
[0172] Preparation Example 7
[0173] The preparation method of this embodiment is basically the same as that of Preparation Example 1, with the only difference being that the thicknesses of the Ni metal layer, the Fe metal layer, and the substrate layer are different. The thicknesses of the Ni metal layer, the Fe metal layer, and the substrate layer in this preparation example are shown in Table 1.
[0174] Preparation Example 8
[0175] Using the base layer as a supporting layer, multiple electroplating of an Fe layer, a Ni layer, an Fe layer, and a Ni layer was performed on the surface of the base layer in sequence to obtain a current collector. From the outer layer to the inner layer of the current collector, the same side surface of the base layer was sequentially provided with a Ni metal layer, an Fe metal layer, a Ni metal layer, and an Fe metal layer. The base layer was the same as that in Preparation Example 1, and the thicknesses of the Ni metal layers and the Fe metal layers are shown in Table 1.
[0176] Preparation Example 9
[0177] The preparation method of this embodiment is basically the same as that of Preparation Example 8, with the only difference being that the thicknesses of the Fe metal layer and the substrate layer are different. The thicknesses of the Fe metal layer and the substrate layer in this preparation embodiment are shown in Table 1.
[0178] Preparation Comparative Example 1
[0179] Copper foil is used as the current collector, and the thickness of the copper foil is 6 μm.
[0180] Preparation Comparative Example 2
[0181] An iron-nickel alloy foil formed by uniformly mixing Ni and Fe is used as a current collector, and the thickness of the iron-nickel alloy foil is 6 μm.
[0182] 2. Current collector performance test
[0183] Breaking strength and elongation at break tests
[0184] The current collector was cut into 100 mm x 15 mm rectangular samples using a die cutter. A tensile test was performed using a tensile machine at a rate of 2 mm / min. The test was terminated when the rectangular sample broke. The tensile strength at break was defined as the breaking strength, and the elongation at break was calculated as the length at break, L1, divided by the initial sample length, L0 - 1. The test data for the breaking strength and elongation at break of the current collectors from the preparation examples and comparative examples are shown in Table 1.
[0185] Table 1
[0186] As shown in Table 1, copper foil has a higher elongation at break but very low fracture strength. The nickel-iron alloy foil has better elongation and fracture strength than copper foil, but iron is easily leached. Preparation Example 1 compares Comparative Example 2 with Preparation Example 2, except that the nickel-iron alloy foil is replaced with a stacked Ni metal layer and Fe metal layer. Due to interlayer slip, the fracture strength of the current collector in Preparation Example 1 is slightly improved.
[0187] Compared to Preparation Example 1, the Ni content in Preparation Example 2 was reduced, the Fe content was increased, and the elongation at break of the current collector decreased, but the fracture strength increased. In Preparation Example 3, the thickness of the current collector was reduced. Since the current collector was thin and easily stretched, the elongation at break was greater, but the fracture strength deteriorated.
[0188] In Preparation Examples 5 and 6, Mo and Cr were used instead of Ni, and the elongation of the current collector decreased, but the strength was improved. In Preparation Examples 8 and 9, the thickness of the current collector was increased, and its elongation decreased, but the strength was significantly improved. In Preparation Examples 1 to 9, a Ni layer, Mo layer, or Cr layer was provided on the outer layer of Fe to provide corrosion protection for the Fe layer.
[0189] 2. Application Examples
[0190] 1. Lithium-ion battery preparation
[0191] Application Example 1
[0192] 1) Preparation of positive electrode sheet
[0193] Nickel-cobalt-manganese (NCM) ternary material, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are added to N-methylpyrrolidone in a mass ratio of 97:1:2, and mixed and stirred for 0.5h to 6h to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector, and the positive electrode sheet is obtained after drying, cold pressing, and slitting.
[0194] 2) Preparation of negative electrode sheet
[0195] The active material artificial graphite, the active material silicon-based material, the conductive agent carbon black, the carbon nanotube (CNT), the binder styrene-butadiene rubber (SBR), and the thickener sodium hydroxymethyl cellulose (CMC) are added to deionized water in a weight ratio of 47.25:47.25:1:0.375:2.8:1.325, and mixed and stirred for 0.5h to 6h to obtain a negative electrode slurry; the silicon-based material accounts for 50% of the active material in the negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector of Preparation Example 1 and dried.
[0196] 3) Isolation film
[0197] Polypropylene film is used as the isolation film.
[0198] 4) Electrolyte
[0199] LiPF6 was dissolved in a mixed solvent of ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate in a volume ratio of 1:1:1 to prepare an electrolyte with a LiPF6 concentration of 1 mol / L.
[0200] 5) Production of lithium-ion batteries
[0201] The positive electrode sheet, separator, and negative electrode sheet are wound in sequence to obtain a bare cell; the bare cell is placed in a packaging shell, dried, and then injected with electrolyte, and a lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping, and other processes.
[0202] Application Example 2
[0203] This application example is basically the same as application example 1, with the only difference being that the silicon-based material accounts for 60% of the active material in the negative electrode slurry, and the total weight of the active material in the negative electrode slurry remains unchanged.
[0204] Application Example 3
[0205] This application example is basically the same as application example 1, with the only difference being that the silicon-based material accounts for 80% of the active material in the negative electrode slurry, and the total weight of the active material in the negative electrode slurry remains unchanged.
[0206] Application Example 4
[0207] This application example is basically the same as application example 1, with the only difference being that the silicon-based material accounts for 100% of the active material in the negative electrode slurry, and the total weight of the active material in the negative electrode slurry remains unchanged.
[0208] Application Example 5
[0209] This application example is basically the same as application example 1, with the only difference being that the negative electrode current collector in the negative electrode plate adopts the current collector prepared in preparation example 4.
[0210] Application Example 6
[0211] This application example is basically the same as application example 1, with the only difference being that the negative electrode current collector in the negative electrode plate adopts the current collector prepared in preparation example 8.
[0212] Application Example 7
[0213] This application example is basically the same as application example 1, with the only difference being that the negative electrode current collector in the negative electrode plate adopts the current collector prepared in preparation example 8.
[0214] Comparative Application Example 1
[0215] This comparative application example is basically the same as the application example 1, with the only difference being that the negative electrode current collector in the negative electrode plate adopts the current collector prepared in the comparative application example 1.
[0216] Application Comparative Example 2
[0217] This comparative example is basically the same as Example 1, with the only difference being that the negative electrode current collector in the negative electrode sheet adopts the current collector prepared in Comparative Example 1; and the silicon-based material accounts for 100% of the active material in the negative electrode slurry, and the total weight of the active material in the negative electrode slurry remains unchanged.
[0218] Application Comparative Example 3
[0219] This comparative application example is basically the same as the application example 1, with the only difference being that the negative electrode current collector in the negative electrode plate adopts the current collector prepared in the comparative preparation example 2.
[0220] 2. Battery performance test
[0221] 1) Fe dissolution concentration
[0222] The battery cells were left at 25°C for 2 hours, discharged at a constant current of 0.1C to 2.0V, and then disassembled. The negative electrode was immersed in DMC solvent for 24 hours, and the Fe content in the DMC solvent that had soaked the negative electrode was measured.
[0223] 2) Energy density
[0224] 2.1) The discharge energy measurement of the battery cell is as follows:
[0225] Let the battery cell stand at 25℃ for 2 hours to ensure the temperature of the battery cell is 25℃;
[0226] After charging the battery cell to the charge cut-off voltage at 0.1C at 25°C, continue constant voltage charging at the charge cut-off voltage until the current reaches 0.05C, and then charge is cut off (where C represents the rated capacity of the battery cell);
[0227] Let the battery cells stand at 25°C for 1 hour;
[0228] At 25°C, discharge the battery cells at 0.1C to the discharge cut-off voltage, and record the total discharge capacity C0 of the battery cells, and the total discharge energy E0;
[0229] 2.2) Battery cell weight measurement: Place the battery cell on an electronic balance until the weight stabilizes, and read the battery cell weight value M0;
[0230] 2.3) Energy density calculation: The energy density of a battery cell is calculated as the discharge energy of the battery cell E0 / the weight of the battery cell M0.
[0231] 3) Fracture ratio of pole piece corners
[0232] The number of negative electrode corners (creases) during the production process of the battery cell is N0
[0233] 3.1) Fully charge both fresh and cycled cells at 0.1C to the charge cut-off voltage, and continue constant voltage charging at the charge cut-off voltage until the current reaches 0.05C, at which point the charge is cut off.
[0234] 3.2) Disassemble the fully charged cells and record the number of anode corner fractures in the cells. The number of fresh cell corner fractures is recorded as N1, and the number of cycled cell corner fractures is recorded as N2.
[0235] 3.3) The ratio of the corner fracture of the fresh battery cell electrode piece is N1 / N0, and the ratio of the corner fracture of the cycled battery cell electrode piece is N2 / N0.
[0236] 4) Cyclic testing process
[0237] The voltage calibration method is as follows:
[0238] 4.1) Let the battery cells stand at 25°C for 2 hours to ensure the temperature of the battery cells is 25°C;
[0239] 4.2) Charge the battery cells to 4.25V at 0.33C0 at 25°C, and then charge at 4.25V constant voltage to a current of 0.05C0;
[0240] 4.3) Let stand for 1 hour;
[0241] 4.4) Discharge the battery at 0.33C0 to 0.95C0 at 25°C and record the voltage V1.
[0242] 4.5) Let stand for 5 minutes;
[0243] 4.6) Discharge to 2.0V at 0.33C0 at 25°C;
[0244] 4.7) Let stand for 5 minutes;
[0245] 4.8) Charge the battery cell at 0.33C0 to 0.97C0 at 25°C and record the voltage V2 at this point.
[0246] 4.9) Let stand for 2 hours.
[0247] The cycle test process is as follows:
[0248] 4.10) Allow the battery cells to stand at 25°C for 2 hours to ensure the temperature of the battery cells is 25°C;
[0249] 4.11) Charge the battery cells to voltage V2 at 0.33C0 at 25°C;
[0250] 4.12) Let stand for 0.5 h;
[0251] 4.13) Discharge the battery cell at 0.33C0 to a voltage of V1 at 25°C. Record the capacity at this point as Cn.
[0252] 4.14) Let stand for 0.5 h;
[0253] 4.15) Repeat steps 4.11 to 4.14 until the number of cycles n reaches 100 cls.
[0254] The above-mentioned test methods were used to perform Fe dissolution concentration test, energy density test, pole piece corner fracture ratio test and cycle test on the lithium-ion batteries of the above application examples and application comparison examples. The test data are shown in Table 2.
[0255] Table 2
[0256] As shown in Table 2, comparing Comparative Examples 1 and 3, the use of Ni+Fe alloy foil as the negative electrode current collector in a high-silicon battery system (e.g., Comparative Example 3) significantly improves battery energy density compared to using copper foil as the negative electrode current collector (e.g., Comparative Example 1). The electrode fracture is also significantly improved, but there is a risk of Fe dissolution. The higher the silicon-based material content in the negative electrode of the battery system, the more pronounced the fracture.
[0257] In Application Example 1, when the content of negative electrode silicon-based material was 50%, no electrode piece fracture occurred in the negative electrode, and the electrode piece fracture ratio was significantly improved compared with copper foil; because the Ni element prevented the corrosion of the Fe element on the surface of the negative electrode current collector, the dissolution of the Fe element was significantly improved compared with Application Example 3, which can extend the service life of the secondary battery.
[0258] In Application Examples 1-4, the battery energy density gradually increased with increasing negative electrode silicon-based material content. The negative electrode sheet fracture rate increased after cycling, but was significantly lower than that of ordinary copper foil. The Fe dissolution concentration increased with increasing negative electrode silicon-based material content, but was significantly lower than that of a uniformly mixed Ni+Fe alloy foil. This demonstrates that the negative electrode current collector of this application has a low fracture rate and Fe dissolution in high-silicon negative electrode secondary batteries, potentially extending the service life of the secondary batteries.
[0259] In Application Example 4, the negative electrode plate breakage ratio is worse than that of the negative electrode silicon-based material content at a ratio of 100%, but it is still improved compared to ordinary copper foil. Due to the repeated shrinkage and expansion of the 100% negative electrode silicon-based material content system, its Fe dissolution is higher than that of the 50% negative electrode silicon-based material content system, but it is still significantly improved compared to the Fe dissolution of the alloy foil with a uniform mixture of Ni+Fe.
[0260] In Application Examples 6 and 7, current collectors with gradient changes in the thickness of the Ni layer and the Fe layer are used. Compared with Application Example 1, under the same negative electrode silicon-based material content conditions, the batteries of Application Examples 6 and 7 have better corrosion resistance, no fracture of the electrode corners, and the dissolution of Fe is further improved, which can further improve the service life of the secondary battery.
[0261] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A current collector, comprising a base layer, a first metal layer and a second metal layer, wherein the first metal layer is arranged on at least one surface of the base layer, the second metal layer is arranged on the surface of the first metal layer away from the base layer, the first metal layer comprises iron or an iron alloy; the second metal layer comprises at least one of a metal layer formed by any one element selected from the group consisting of copper, tin, lead, molybdenum, chromium and nickel, a single metal laminate formed by any two or more elements and an alloy layer formed by any two or more elements.
2. The current collector according to claim 1, characterized in that: A plurality of first metal layers and a plurality of second metal layers are alternately arranged on the same side surface of the base layer, and the outermost layer of the current collector is the second metal layer.
3. The current collector according to claim 2, characterized in that: In a direction from the base layer to the outermost layer, the thicknesses of the multiple layers of the first metal layers on the same side surface of the base layer are equal or decrease in sequence.
4. The current collector according to claim 2 or 3, characterized in that: In a direction from the base layer to the outermost layer, the thicknesses of the multiple first metal layers on the same side surface of the base layer decrease successively, and the thickness difference between two adjacent first metal layers is 0.5 μm to 1.0 μm.
5. The current collector according to any one of claims 2 to 4, characterized in that: In a direction from the base layer to the outermost layer, the thicknesses of the multiple layers of the second metal layers on the same side surface of the base layer are equal or increase in sequence.
6. The current collector according to any one of claims 2 to 5, characterized in that: In a direction from the base layer to the outermost layer, the thicknesses of the multiple layers of the second metal layers on the same side surface of the base layer increase successively, and the thickness difference between two adjacent layers of the second metal layers is 0.5 μm to 1.0 μm.
7. The current collector according to any one of claims 1 to 6, characterized in that: The base layer includes iron alone or an iron alloy.
8. The current collector according to any one of claims 1 to 7, characterized in that: The material of the base layer is the same as that of the first metal layer, and the material of the base layer is different from that of the second metal layer.
9. The current collector according to any one of claims 1 to 8, characterized in that: The current collector satisfies at least one of the following (1) to (3): (1) The substrate layer is an iron metal layer; (2) The first metal layer is an iron metal layer; (3) The second metal layer is a nickel metal layer.
10. The current collector according to any one of claims 1 to 9, characterized in that: The thickness of the substrate layer is 2 μm to 6 μm; Optionally, the base layer has a thickness of 2 μm to 4 μm.
11. The current collector according to any one of claims 1 to 10, characterized in that: The thickness of the current collector is 4 μm to 20 μm; Optionally, the current collector has a thickness of 6 μm to 9 μm.
12. The current collector according to any one of claims 1 to 11, characterized in that: The thickness of the first metal layer is 0.5 μm to 16 μm; Optionally, the first metal layer has a thickness of 0.5 μm to 1.5 μm.
13. The current collector according to any one of claims 1 to 12, characterized in that: The thickness of the second metal layer is 0.5 μm to 16 μm; Optionally, the second metal layer has a thickness of 0.5 μm to 1.5 μm.
14. A method for preparing a current collector, comprising the following steps: providing a base layer; forming a first metal layer on a surface of the base layer; and forming a second metal layer on a surface of the first metal layer facing away from the base layer; in, The first metal layer includes iron or an iron alloy, and the second metal layer includes at least one of a metal layer formed by any one element of copper, tin, lead, molybdenum, chromium and nickel, a single metal stack formed by two or more elements, and an alloy layer formed by two or more elements. 15 . A secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector, and the negative electrode current collector comprises the current collector according to any one of claims 1 to 13.
16. The secondary battery according to claim 15, characterized in that: The negative electrode current collector is provided with a negative electrode active material, the negative electrode active material contains a silicon-based material, and the mass fraction of the silicon-based material in the negative electrode active material is 25% to 100%.
17. An electrical device comprising the secondary battery according to claim 15 or 16.